Job-to-Job Transitions, Sorting, and Wage Growth - David Jinkins; Annaig Morin (Institute of Labor Economics (IZA), 2017)
We measure the contribution of match quality to the wage growth experienced by job movers. We reject the exogenous mobility assumption needed to estimate a standard fixed-effects wage regression in the Danish matched employer-employee data. We exploit the sub-sample of workers hired from unemployment, for whom the exogenous mobility assumption is not rejected, to estimate firm fixed effects. We then decompose the variance of wage growth of all job movers. We find that 66% of the variance of wage growth experienced by job movers can be attributed to variance in match quality. Expected match quality growth is higher for higher-skilled occupations.
Keywords: J62; J63; C23; 330; job mobility; fixed-effect wage models; assortative matching; panel data models